Desencontro marcado? Desapropriação, eficiência administrativa e absolutismo proprietário no Brasil (1826-1930) - Arthur Barrêtto de Almeida Costa (2019)
Historiography thinks of the nineteenth century as a time when State prerogatives are exacerbated but, equally, of absolutization of property. Through the analysis of expropriation, this dissertation put these two conclusions into perspective, and try to identify how they can be reconciled. To tackle this objective, the major national legislative interventions on the subject were scrutinized, coupled with the respective parliamentary debates, public law books, discussions in the daily press and 466 court rulings and 42 legal opinions taken from 12 legal journals. It was possible to identify the existence of three models of expropriation over the period which coexisted. The first derives from the 1826 act, is based on the distinction between public utility and public necessity and is projected to be hard to execute. The second arises with the 1845 act and institutes the expropriation jury; it is a little easier to carry out, but still generates high compensations. From the 1850s on, with the economic development of the country, a greater presence of the State was demanded, and a new model was created, based on a special decree in 1855. It was successively employed in small urban reforms in Rio de Janeiro and in the construction of railroads. This progressive flexibilization was facilitated by two parliamentary strategies: the creation of legislative regimes of exception, with faster kinds of expropriation; and the second was the presentation of sketchy projects, of faster discussion, which diminished the opportunities for filibuster for the opposition. In 1904, with the major urban reform in Rio de Janeiro in view, the complex provisions then in force were consolidated and simplified. Parallel to this legislative path, an attempt was made in late 19th century to use expropriation for a smooth abolition of slavery, but the proponents of this solution were unsuccessful. Hence the first conclusion: the development of the institute was primarily related to the needs of urban reforms and, to a lesser extent, to the construction of railroads. The analysis of legal journals led to additional results. The second conclusion, then, is the existence of a disjunction between a doctrinal and judicial discourse that demonizes expropriation, despite considering it necessary, and, on the other hand, a forensic practice that shows landowners profiting from expropriations through negotiation with the State. The third is that expropriations cannot be viewed solely as a conflict between the State and private individuals, since most of them are promoted by private companies authorized by the public authorities. The fourth conclusion is that in the twentieth century, laws are made with the objective of accelerating state intervention, but judges oppose this objective by expanding the opportunities for discussion of various issues within the process. The fifth is that Brazilian jurists constantly refer to foreign authors, especially French ones, but when "translating" their ideas into Brazilian law, they have built a system that is progressively more favorable to the State. In general terms, it is possible to say that, between 1826 and 1930, the Brazilian legal system was providing the State with increasingly efficient means to intervene in property; but this intervention could in certain cases violate the right to property, or, in very specific ones, serve the hidden interests of a minority of well-connected owners.